EDUKASI MITIGASI DAN ADAPTASI PERUBAHAN IKLIM PADA KELOMPOK TANI TARUKO SAIYO MELALUI AGENDA SEKOLAH LAPANG IKLIM DI KOTA PADANG - Nugraha Ramadhan; Muhsanati Muhsanati; Dini Hervani; Obel Obel; Afrima Sari; Rachmad Hersi Martinsyah; Ronaldi Ronaldi; Ilhan Pahlevi; Syahrul Utama; Azri Gilang Ramadhan Daulay; Rizki Nia Sukri Nasution; Fala Adifki Mashel (Jurnal Hilirisasi IPTEKS, 2024)
The Taruko Saiyo Farmer Group is a community-based farmer initiative that comprises and grows based on harmony, warmth, and shared interests in utilizing agricultural resources to collaborate in improving the productivity of agricultural enterprises, especially in increasing rice production. Given the strong desire of the members of the Taruko Saiyo farmer group to tackle the issues arising from climate conditions and feeling the need to be accompanied due to a lack of science and technology knowledge regarding climate change mitigation and adaptation, it is appropriate as a partner to support the desires of these farmers and to provide guidance until they can master the science and technology and become an independent farmer group. The purpose of this project is: 1) To help farmers understand climate information and forecasts to support agricultural activities, particularly for planting season decisions and the right technical cultivation strategies as an effort to increase product quantity, 2) To enhance science and technology knowledge and management skills of farmers in managing agricultural waste as support for farming activities, as well as to form an awareness of climate conditions. This community service activity is carried out from June to September 2024. Some of the agendas in this climate field school program include socialization, training, application of science and technology, mentoring, and evaluation. Based on the evaluation results, around 90% of the partner members felt an increase of about ≥80% in understanding, management, science and technology implementation, and production quantity. With ongoing support and active participation from various parties, it is hoped that this program can become a model for sustainable agriculture development.